Prof. Jang-Ming Lee: single-incision minimally invasive esophagectomy (MIE), better recovery for patients - Shih, Tung-Lun (Journal of Thoracic Disease; Vol 10, No 1 (January 31, 2018): Journal of Thoracic Disease, 2017)
Dr. Jang-Ming Lee (Figure 1) is not only a speaker but also a host for several presentations in the 16th annual meeting of Taiwan Association of Thoracic & Cardiovascular Surgery (TATCS), which was held on October 28 and 29 in Taipei. The topic he shared is “Per-oral endoscopic myotomy (POEM) for treating esophageal achalasia: the NTUH experience.” The POEM is a minimally invasive surgical procedure for the treatment of achalasia wherein the inner circular muscle layer of the lower esophageal sphincter is divided through a submucosal tunnel, which enables food and liquids to pass into the stomach that is impaired in achalasia (cited from Wikipedia).